Moral distress in Iranian nurses' experiences - Khodaveisi, masoud; Hassani, parkhideh (Advances in Nursing & Midwifery, 2013)
Abstract Background & Aim: Ethics is an integral part of nursing practice. Nurses and other professional caregivers are increasingly recognizing the issue of moral distress. The aim of this study is to describe Iranian nurses' experiences in moral distress. Materials and Method : In this study the qualitative phenomenological approach was used. 11 nurses from teaching hospitals of Hamadan University of Medical Sciences participated in the study. The data were collected by in-depth interviews. Transcripts were analysed by constant comparative contant analysis. Result: The results sorted into 4 content areas: individual characteristics of team care (including knowledge, ability, experience, responsibility and…), mental-affective reactions (including faulty, defensive reactions, lack of motivation and…), laws and officials (including, limitation of laws and contradictory of laws with ethics, religion, knowledge and ability) and circumstances of workplace (including physical circumstances, manpower, facilities and equipments). Conclusion: It is necessary that nurses become familiar with ethical problems, nursing code of ethics and promote the skills for encounter to moral distress. Key words: Ethics, Moral distress, Nursing practice, Experience, Phenomenology Corresponding Author: Parkhideh Hasani, Faculty Lecturer, Department of Anesthesiology, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences,Tehran, Iran Email: p_hasani@sbmu.ac.ir REFERENCES - Forum. 17 (1) 33–48. - - - - - - - - - - - - - - - - - - - edition. Philadelphia: Lippincott. - Wilkinson JM (1987). Moral distress in nursing practice: Experience and effect. Nursing Forum. 23(1) 16-29. Streubert HJ Carpenter DR (2007). Qualitative Research in Nursing Advancing the Humanistic Imperative. 3 rd Van Manen M (2001). Researching Lived Experience. Action Sensitive Pedagogy 3rd edition. Ontario: Althouse Press. Silen Marit et al (2008). Workplace distress and ethical dilemmas in neuroscience nursing. Journal of Neuroscience Nursing. 40(4) 222-231. Pijl-Zieber EM et al (2008) . Moral distress: An emerging problem for nurses in long-term care. Quality in Ageing and Older Adults. 9(2) 39- 48. Oskouie F pairovi H (2005). [Qualitative Research in Nursing]. 1st edition. Tehran: Iran University of Medical Sciences Press. (Persian). Oberle k Hughes D (2001). Doctors and nurses perceptions of ethical problems in end-of-life decisions. Journal of Advanced Nursing. 33(6) 707-715. Nathaniel A (2002). Ethics and human rights. The American Nurses Association Issues Update. 1(2) 3-8. Mitchell GJ (2002). Policy, procedure and routine: Masters of moral influence. Nursing Science Quarterly. 14(2) 109- 114 McVicar A (2003). Workplace stress in nursing: A Literature review. Journal of Advanced Nursing. 44(6) 633-642. Mauleon AL Palo Bengtsson L Ekman SL (2005). Anaesthesia care of older patients as experienced by nurse anaesthetists. Nursing Ethics. 12(3) 263–272. Herting A et al (2004). Downsizing and reorganization: Demands, challenges and ambiguity for registered nurses. Journal of Advanced Nursing. 45(2) 145-154. Jameton A (1993). Dilemmas of moral distress: Moral responsibility and nursing practice. AWONN’s Clinical Issues in Prenatal and Women Health Nursing. 4(4) 542-551. Gutierrez KM (2005). Critical care nurses’ perceptions of and responses to moral distress. Dimensions of Critical Care Nursing. 24(5) 229–241. Chitty Kay K Beth BP (2007). Professional Nursing Concepts. Challenge. Saunders Elsevier Ebrahimi H et al (2007). [Stress: Major reaction of nurses to the context of ethical decision making]. Journal of Iran University of Medical Sciences. 14(54) 7-15 (Persian). Cronqvist A Lutzen K Nystrom M (2006). Nurses’ lived experience of moral stress support in the intensive care context. Journal of Nursing Management. 14(5) 405-413. Corley M et al (2001). Development and evaluation of a moral distress scale. Journal of Advanced Nursing. 33(2) 250-256. Corley M (2002). Moral distress: A proposed theory and research agenda. Nursing Ethics. 9 (6) 636-650. Canadian Nursing Association (2002). Code of ethics for registered nurses. Ottawa: Author. [On line]. http://www.nurses.ab.ca/Carna-Admin/Uploads/CNAcodeofEthics.pdf Canadian Nurses Association (2003). Ethics in Practice for Registered Nurses. [On line]. http://www2.cnaaiic. ca/CNA/documents/pdf/publication/Ethics_in_Practice. Austin W et al (2005). Moral distress in healthcare practice: the situation of nurses. Health care ethics committee